A simple Mathematical Fuzzy Model of Brain Emotional Learning to Predict Kp Geomagnetic Index - Lotfi, Ehsan; Keshavarz, A. (International Journal of Intelligent Systems and Applications in Engineering, 2014)
In this paper, we propose fuzzy mathematical model of brain limbic system (LS) which is responsible for emotional stimuli. Here the proposed model is utilized to predict the chaotic activity of the earthâs magnetosphere. Numerical results show that the correlation of the results obtained from the proposed fuzzy model is higher than non-fuzzy models. Hence, the proposed model can be applied in real time chaotic time series prediction.